Prognostic factors in chronic lymphocytic leukemia - Hayat, Amjad (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Haematology, 2008)
Chronic lymphocytic leukaemia (CLL) is the most common leukaemia in the Western world, accounting for nearly 24% of all leukaemias. It is estimated that 7300 new cases were diagnosed in 2003 in the United States and there were 4400 deaths due to CLL. At diagnosis, many patients are asymptomatic but subsequently develop symptoms and die from the disease or its complications.
Keywords: Haematology, Ph.D.; Ph.D. Trinity College Dublin